Pemetaan Tingkat Manipulasi Laporan Keuangan pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia selama Covid-19 - Robith Hudaya; Nungki Kartikasari; Adhitya Bayu Suryantara (Valid: Jurnal Ilmiah, 2021)
The coronavirus pandemic or better known as COVID-19 has had an impact on many sectors. One of the sectors that has been badly affected by COVID-19 is the economic sector. Every manager is required to meet the performance targets that have been made in early 2020. The problem is, COVID 19 causes economic instability so that the initial target will be difficult to achieve. As a result, the potential for manipulative actions on the financial statements from the company's management will be higher so that the target is achieved. This study aims to mapping manufacturing companies that manipulate their financial statements using the benefit m score model during 2020. In addition, it will examine which manipulative companies are in a state of financial difficulty leading to bankruptcy. To achieve the research objectives, a study will be conducted using descriptive analysis methods. The results of this study found that manufacturing companies listed on the Indonesia Stock Exchange on average did not manipulate their financial statements in the Covid-19 pandemic. Companies that did not manipulate the financial statements in 2020 were 78.8% or 145 companies. Companies with grey area status or companies that are likely to manipulate financial statements in 2020 are 4.3% or 8 companies and companies that manipulate financial statements in 2020 are 16.8% or as many as 31 companies. In addition, of the 31 companies that carried out the manipulation, there were 6 companies that had the potential to go bankrupt.